Black diamond dust - Birch, Jesse; Holder, Will 1969- (Sternberg Press, 2017)
This publication expands a 2014 multisite contemporary art exhibition that took place in Nanaimo, British Columbia, a small city on the eastern edge of Vancouver Island. The title refers to coal mining, an industry that has formed and fragmented communities through economic development, racial segregation, and labor inequity, while fueling the modern world. In this book, forgotten or under-acknowledged histories are investigated and discussed along with cultural forms that surround the practices of international coal mining. Contemporary artworks, poetry, essays, literature, folk songs, and archival images come together to extract meaning from this fossilized black carbon that continues to power our cities.